THE IDEA OF REGULATING OF GOVERNOR’S AUTHORITY AS GOVERNMENT’S REPRESENTATIVE POST THE AMENDMENT OF 1945 CONSTITUTION (GAGASAN PENGATURAN KEWENANGAN GUBERNUR SEBAGAI WAKIL PEMERINTAH SETELAH PERUBAHAN UNDANG UNDANG DASAR 1945) - Yuslim, Yuslim (Yustisia, 2013)
AbstractThe idea of regulating of governor’s authority as representative of central government to the regency/ town government after the amendment of 1945 constitution is aimed at answering two legal problems. They are: (1) How is the regulation of the authority of governor as representative of central government after the amendment of 1945 constitution, (2) How is the idea governor as the representative of government. In order to answer such a questions the research   conducted by using legal/normative research. The approach that used is statue approach and conceptual approach. The regulating of governor’s authority as representative of central government as stipulated in Art. 32 of Act No.32 year of 2004 do not have firm validity in 1945 Constitution. Such the authority of governor is conducted as the implementation of principle of de-concentration, while such a principle does not clearly formulated in 1945 constitution. Besides it does not have constitution’s validity, the regulating of governor’s authority in Act No.32, 2004 does not have clear concept since on one hand such authority is attribution, an on one hand that authority is a delegation and even in practice it is a mandate. According of Unitary state’s point of view the authority of governor as direct representative of central government  after the amendment of 1945 constitution should be in delegation form. Therefore it is not directly enumerated in Act regarding the Local government (attribution).The president that would transfer that authority in government regulation (pp). The delegation of authority to the governor should cover the affair of general government in province, so it is not just limited to a certain affair.Besides in conducting the authority, the governor as representative of central government needs certain organ that assist the governor in performing his authority and as the organ of central government.Key word: The idea, governor’s authority, government’s representat, unitary state.AbstrakGagasan penaturan kewenangan gubernur sebagai wakil pemerintah terhadap kabupaten/ kota setelah perubahan Undang-Undang Dasar 1945 bertujuan menjawab 2(dua) problem hukum, yakni :   (1) Bagaimana pengaturan kewenangan gubernur sebagai wakil pemerintah setelah perubahan UUD 1945, dan (2) Bagaimana gagasan kewenangan gubernur sebagai wakil pemerintah. Untuk menemukan jawaban pertanyaan yang muncul dilakukan penelitian hukum normatif dengan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Pengaturan kewenangan gubernur sebagai wakil pemerintah dalam Pasal 38 UU No. 32/2004 tidak memiliki validasi yang tegas dalam UUD 1945.Kewenangan gubernur tersebut dilakukan dalam rangka pelaksanaan asas dekonsentrasi, sementara asas dekonsentrasi tidak dirumuskan secara tegas dalam UUD 1945.Selain tidak memiliki validasi konsitusi, pengaturan kewenangan gubernur dalam UU No. 32/2004 tidak jelas konsepnya karena satu sisi kewenangan tersebut berupa atribusi, pada bagian lain berupa delegasi dan bahkan dalam praktek berupa mandat. Menurut sudut pandang sistem negara kesatuan (unitary state) kewenangan gubernur sebagai wakil pemerintah langsung setelah perubahan UUD 1945 haruslah berupa delegasi kewenangan.Jadi tidak ditegaskan (dirinci) langsung dalam UU mengenai pemerintahan daerah (atribusi). Presiden yang akan melimpahkan kewenangan tersebut nantinya dalam Peraturan Pemerintah. Pelimpahan kewenangan kepada gubernur tersebut ruanglingkupnya haruslah mencakup urusan pemerintahan umum di provinsi jadi tidak dibatasi pada urusan tertentu saja.Selain itu dalam menjalankan kewenangan gubernur sebagai wakil pemerintah perlu organ tertentu yang membatu gubernur dalam menjalankan kewenangannya dan merupakan organ pemerintah.Key word: Gagasan, Kewenangan Gubernur, Wakil Pemerintah, Negara Kesatuan.